Oxidation induced restructuring of Rh-Ga SCALMS model catalyst systems - Wittkämper, Haiko; Maisel, Sven; Wu, Mingjian; Frisch, Johannes; Wilks, Regan G.; Grabau, Mathias; Spiecker, Erdmann; Bär, Marcus; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (Journal of Chemical Physics, 2020)
Supported catalytically active liquid metal solutions have been receiving increasing attention recently. We investigated the oxidation behavior of macroscopic Rh-Ga alloy droplets and Rh-Ga model catalyst nanoparticles supported on SiO2/Si(100) with low Rh content (<2.5 at. %) by x-ray photoelectron spectroscopy in ultra-high vacuum and under near-ambient pressure conditions using different photon energies and also using transmission electron microscopy. The experiments are accompanied by computational studies on the Ga oxide/Rh-Ga interface and Rh-Ga intermetallic compounds. For both Rh-Ga alloy droplets and Rh-Ga model catalyst nanoparticles, exposure to molecular oxygen leads to the formation of an oxide shell in which Rh is enriched. Transmission electron microscopy on the Rh-Ga nanoparticles confirms the formation of an ∼4 nm thick gallium oxide film containing Rh. Based on ab initio molecular dynamics and computational studies on the Ga2O3/Ga interface, it is concluded that Rh incorporation into the Ga2O3 film occurs by substituting octahedrally coordinated Ga.
CRIS-Team Scopus Importer:2020-09-25